Induction of Osmolyte Pathways in Skeletal Muscle Inflammation: Novel Biomarkers for Myositis - De Paepe, Boel; Zschüntzsch, Jana; Šokčević, Tea; Weis, Joachim; Schmidt, Jens; De Bleecker, Jan L. (Frontiers in Neurology, 2018)
We recently identified osmolyte accumulators as novel biomarkers for chronic skeletal muscle inflammation and weakness, but their precise involvement in inflammatory myopathies remains elusive. In the current study, we demonstrate in vitro that, in myoblasts and myotubes exposed to pro-inflammatory cytokines or increased salt concentration, mRNA levels of the osmolyte carriers SLC5A3, SLC6A6, SLC6A12, and AKR1B1 enzyme can be upregulated. Induction of SLC6A12 and AKR1B1 was confirmed at the protein level using immunofluorescence and Western blotting. Gene silencing by specific siRNAs revealed that these factors were vital for muscle cells under hyperosmotic conditions. Pro-inflammatory cytokines activated mitogen-activated protein kinases, nuclear factor κB as well as nuclear factor of activated T-cells 5 mRNA expression. In muscle biopsies from patients with polymyositis or sporadic inclusion body myositis, osmolyte pathway activation was observed in regenerating muscle fibers. In addition, the osmolyte carriers SLC5A3 and SLC6A12 localized to subsets of immune cells, most notably to the endomysial macrophages and T-cells. Collectively, this study unveiled that muscle cells respond to osmotic and inflammatory stress by osmolyte pathway activation, likely orchestrating general protection of the tissue. Moreover, pro-inflammatory properties are attributed to SLC5A3 and SLC6A12 in auto-aggressive macrophages and T-cells in inflamed skeletal muscle.